Family Reunion (Raton Range Raton, New Mexico, 1975)
Newspaper Article on the family reunion of Mr. and Mrs Nicanor Castillo and their 7 children.
Master list item #: 13
File location is in the Raton File Cabinet
Keywords: Castillo, Nicanor; Castillo, (Mrs.); Castillo, Ralph; Castillo, Luciano; Castillo, Mary; Castillo, Isabel; Castillo, Alvino; Castillo, Viola; Castillo, Phyllis; Local History; Biography; Life and Customs; Family; Reunion; Raton, New Mexico